Effect of oral administration of methanolic extract of Ocimum gratissimum on intestinal ischemia-reperfusion injury in Rats (2013)
Aim: The effect of the methanolic extract of Ocimum gratisimum (OG) leaves on thetissue damage induced by ischemia-reperfusion (IR) injury in the rat intestine wasinvestigated. Study Design: Randomized controlled experiment.Place and Duration of Study: Experimental Animal Unit and Faculty of VeterinaryMedicine, University of Ibadan, Nigeria from March to May, 2013. Methodology: 18 rats were divided randomly into 3 groups of 6 rats each. Group I served as control; Group II had IR injury by laparotomy with clamping of the Superior mesenteric artery (SMA) for 30 minutes followed by removal of the clamp for 45 minutes; Group III was pre-treated orally for 7days with methanolic extract of Ocimum gratissimum (MEOG)followed by IR injury. Sections of the duodenum and ileum were cut for histopathological examination. The remaining tissues were processed for the determination of biochemical markers of oxidative stress including Hydrogen peroxide (H2O2), Malondialdehyde (MDA) and Glutathione concentrations. Results: Mean values of MDA and H2O2 levels were significantly elevated (P=0.004 and P=0.03, respectively) in intestinal tissues following IR compared to control while reduced glutathione (GSH) levels were not significantly altered. OG (500mg/kg) caused significant reduction (P=0.02 and P=0.04) in MDA concentrations and H2O2 generation, respectively compared with the IR group. Histopathological examination revealed erosions and stunting of the villi tips in the duodenum and ileum, with severe mononuclear infiltration at the mucosal surface in the IR group. No visible lesions were observed in the intestine of the control group, with no significant alterations in the intestinal epithelium of the OG-treated rats. Conclusion: The results suggest that OG may provide some protection against intestinal mucosal injury induced by ischemia-reperfusion, through its anti-oxidative effects.